Highly accurate multiprotein detection on a digital ELISA platform. Issue 16 (6th July 2022) - Yang, Shih-Mo; Bi, Qingbo; Zhang, Wen Jun; Cui, Xiaochuan; Zhou, Ying; Yuan, Cunyin; Cui, Yubao
Abstract : The emerging single-molecule detection platform digital enzyme-linked immunosorbent assay (ELISA) can detect numerous proteins simultaneously at serum concentrations as low as picograms per milliliter. Abstract : The emerging single-molecule detection platform digital enzyme-linked immunosorbent assay (ELISA) can detect numerous proteins simultaneously at serum concentrations as low as picograms per milliliter. We sought to improve cytokine detection with this platform to aid diagnosis of conditions such as allergy and asthma. We developed a multiple single-molecule detection digital ELISA approach, through the application of encoded magnetic microbeads to simultaneously detect three cytokines in one serum sample. We tested the approach's utility to distinguish asthma-related cytokines in children. Concentrations of interleukin-4 (IL-4) and IL-6 were significantly higher in children with asthma than in healthy controls, while the concentration of interferon-γ (IFN-γ) was significantly lower. Our method has higher accuracy than conventional methods, and our results indicate that the proposed improved high-sensitivity digital ELISA-based diagnosis approach can facilitate early detection and treatment of childhood asthma or related diseases.